Ethnobotanical assessment of antidiabetic medicinal plants in District Karak, Pakistan - Amina Nazar; Muhammad Adnan; Syed Majid Shah; Ahmed Bari; Riaz Ullah; Akash Tariq; Nisar Ahmad (BMC, 2024)
Abstract Background Diabetes is a leading health disorder and is responsible for high mortality rates across the globe. Multiple treatment protocols are being applied to overcome this morbidity and mortality including plant-based traditional medicines. This study was designed to investigate the ethnomedicinal status of plant species used to treat diabetes in District Karak, Pakistan. Materials and methods A semi-structured survey was created to collect data about traditionally used medicinal plants for diabetes and other ailments. The convenience sampling method was applied for the selection of informants. The collected data was evaluated through quantitative tools like frequency of citation (FC), relative frequency of citation (RFC), informant consensus factor (FIC), fidelity level (FL), and use value (UV). Results A total of 346 local informants were selected for this research. Out of them, 135 participants were men and 211 participants were women. Overall 38 plant species belonging to 29 plant families were used to treat diabetes. The most dominant plant family was Oleaceae having 11 species. Powder form (19%) was the most recommended mode of preparation for plant-based ethnomedicines. Leaves (68%) were the most frequently used parts followed by fruit (47%). The highest RFC was recorded for Apteranthes tuberculata (0.147). The maximum FL was reported for Apteranthes tuberculata (94.4) and Zygophyllum indicum (94.11) for diabetes, skin, and wounds. Similarly, the highest UV of (1) each was found for Brassica rapa, Melia azedarach, and Calotropis procera. Based on documented data, the reported ailments were grouped into 7 categories. The ICF values range between 0.89 (diabetes) to 0.33 (Cardiovascular disorders). Conclusion The study includes a variety of antidiabetic medicinal plants, which are used by the locals in various herbal preparations. The species Apteranthes tuberculata has been reported to be the most frequently used medicinal plant against diabetes. Therefore, it is recommended that such plants be further investigated in-vitro and in-vivo to determine their anti-diabetic effects.